On the role of ex post uncertainty assessment for risk management. (3rd June 2005) - Heinzl, Harald; Mittlboeck, Martina; Edler, Lutz
A risk management decision whether a chemical compound present in the environment is potentially hazardous to human health will be among others based on large-scaled statistical analyses of empirical data of various sources. Observations from highly exposed and well-documented occupational cohorts are usually a matter of particular interest. Due to scientific progress, various new aspects will inevitably emerge in the course of time. These new aspects are not always in full accordance with the assumptions of the original statistical analyses so that concern may evolve as to whether the original foundation of the risk assessment is still valid, in the main. We suggest accounting for such doubts by an ex post uncertainty assessment of the original statistical analyses. The case of the risk assessment as to whether 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) is a human carcinogen is used as an example. We call for the scheduling of future ex post uncertainty assessments at the time of the risk management decision.